2013
DOI: 10.1177/1941738113481200
|View full text |Cite
|
Sign up to set email alerts
|

Core Stability Training for Injury Prevention

Abstract: Context:Enhancing core stability through exercise is common to musculoskeletal injury prevention programs. Definitive evidence demonstrating an association between core instability and injury is lacking; however, multifaceted prevention programs including core stabilization exercises appear to be effective at reducing lower extremity injury rates.Evidence Acquisition:PubMed was searched for epidemiologic, biomechanic, and clinical studies of core stability for injury prevention (keywords: “core OR trunk” AND “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
158
0
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(173 citation statements)
references
References 60 publications
0
158
0
15
Order By: Relevance
“…1 Core stability exercises have become a popular form of therapeutic exercise and are seen as a critical component to restoring proper kinetic function. 2 However, evidence to support their use and draw definitive conclusions is lacking. 1,2 Further complicating the treatment of LBP are the lack of a universal definition of core stability and the disputed accuracy of clinical tests used to identify an unstable core.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 Core stability exercises have become a popular form of therapeutic exercise and are seen as a critical component to restoring proper kinetic function. 2 However, evidence to support their use and draw definitive conclusions is lacking. 1,2 Further complicating the treatment of LBP are the lack of a universal definition of core stability and the disputed accuracy of clinical tests used to identify an unstable core.…”
mentioning
confidence: 99%
“…2 However, evidence to support their use and draw definitive conclusions is lacking. 1,2 Further complicating the treatment of LBP are the lack of a universal definition of core stability and the disputed accuracy of clinical tests used to identify an unstable core. 1 In their systematic review, Wang et al 3 found that core exercises produced better outcomes than general exercise during the initial 3 months of intervention for LBP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidences suggest that lumbar-pelvic disorders are more often caused by changes in muscle recruiting (time, amplitude and resistance) than by changes in muscle force 1,2 . Lumbar-pelvic stability contributes to the control of movements of the trunk and pelvis in relation to the lower extremities; allowing, thus, the production, dissipation and transfer of power during the movement 1,2 . Therefore, lumbar-pelvic instability is considered a risk factor for the onset of lumbar pain, postural changes and structural degenerative processes 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…The stability of the lumbar-pelvic complex aims to maintain the balance of the spine within physiological limits, in order to protect structural integrity and reduce dislocation caused by disturbances 1 . Evidences suggest that lumbar-pelvic disorders are more often caused by changes in muscle recruiting (time, amplitude and resistance) than by changes in muscle force 1,2 .…”
Section: Introductionmentioning
confidence: 99%